Sero-Epidemiology of Avian Influenza Virus in Native Chicken in Bangladesh - Nooruddin, G.M.; Hossain, M.T.; Mohammad, M.; Rahman, M.M. (International Journal of Poultry Science, 2006)
Sero-epidemiological investigation was carried out to determine avian influenza virus in native chickens at Dagonbhuyian, Feni district in Bangladesh. A total of 224 sera samples were collected from the chickens of key beneficiaries during monsoon, winter and summer seasons. All sera samples were examined for the detection of antibodies of Avian influenza virus by indirect enzyme linked Immunosorbant assay using commercially available Kits. The seroprevalence was found 25% in Ram Nagar union, 14.28% Matubhuyian union, 0% in Rajapur union and 0% Jaylashker union. The overall seroprevalence of avian influenza was recorded 9.82%. Sero-epidemiology of virus in relation to seasonal variation was also carried out in the study areas and it was recorded 14.45% during monsoon, 3.70% during winter and 11.67% during summer season. The investigation exhibited higher prevalence of avian influenza in hens (10.83%) than cocks (8.65%). The investigation revealed the highest (12.80%) prevalence in birds > 34 weeks of age group and the lowest (3.13%) in birds of 8-16 weeks of age. However, Quick antigen detection kit for avian influenza virus identification did not show positive results of the samples collected for virological study.